The Effect of Curcumin Adjuvant Therapy on Pulmonary Function and Levels of Interleukin-6 (IL-6) and Superoxide Dismutase-3 (EC-SOD3) in Patients with Chronic Bronchial Asthma - Sura Abbas Khdair; Manal Khalid Abdulridha; Mostafa Abdalfatah Shafek (Indonesian Journal of Pharmacy, 2021)
This study was designed to evaluate the effectiveness of curcumin supplement as antioxidant and anti-inflammatory in patients with chronic bronchial asthma. Forty patients diagnosed with chronic bronchial asthma were enrolled in this study and allocated into group (1) patients   assigned to receive conventional therapy of asthma, and group (2) patient assigned to receive conventional therapy of asthma combined with 750 mg curcumin supplement twice daily for two months. Pulmonary function test, asthma control test, serum interleukin-6 and serum extracellular super oxide dismutase 3 were measured before and after two months in both study groups. After two months, the mean values of pulmonary function test (spirometry) and asthma control score showed significant increase compared to pre-treatment values in group 2 patients (P<0.01). Moreover, there was marked decrease in the level of interleukin-6 in group 2 patients after two months (p< 0.05) compared to the increased in group 1 patients. The mean level of super oxide dismutase 3 didn’t show any increase in both study groups after treatment. Curcumin supplement produced improvement in pulmonary function of patients with chronic bronchial asthma along with the reduction in inflammatory status. No change in endogenous oxidative status after curcumin supplementation.